THE EVALUATION OF TEACHER PROFESSIONAL DEVELOPMENT PROGRAM IN BUIN BATU JUNIOR HIGH SCHOOL, WEST SUMBAWA - Boko, Kristyanto Sidkenu (Journal of Education Research in Administration and Management (JERAM), 2017)
This study aimed at evaluating the teacher professional development (Teachers’ PD) program in SMP Buin Batu, West Sumbawa. It was a program evaluation using descriptive method and CIPP model. Each teacher PD program data collected through participant communication using interview, observation, and document study and evaluated on it context, input, process, and product (CIPP). The data evaluation indicated that: 1) training need, objective and target are met all indicators 2) human resources, facilities, budget and policy met 96% of all indicators 3) planning, organizing, monitoring and feedback met 95% all indicators 4) achievement, sustainability and outcome achieved 87,5% of all indicators. The findings lead to recommendation to create dynamic mentoring program of new teacher, manage teachers ‘ownership to improve their English skill, involve PTNNT Training Department to improve teachers’ leadership skill, and implement professional learning transference.